Digital Exclusion Despite Digital Accessibility: Empirical Evidence from an English City. (5th November 2013) - Bunyan, Sabrina; Collins, Alan
Abstract: This study provides a high resolution investigation into the socio‐economic determinants of digital exclusion, within a single, densely populated city, where access is less likely to be a barrier to users. It employs data drawn from a representative interview survey of 1, 005 households from across the city of Portsmouth, UK. In this study digital exclusion refers to those individuals who do not use the internet either at home, work, place of study or elsewhere. Multivariate statistical analysis identifies those significant factors raising or depressing the probability of being categorised as digitally excluded including, inter alia, age, gender, income, education, disability, tenure, working status, the presence of young people in the household and city neighbourhood districts ('super groups').